PENGARUH GREEN INTELLECTUAL CAPITAL, GREEN HUMAN RESOURCE MANAGEMENT, DAN GREEN INNOVATION TERHADAP KINERJA KEBERLANJUTAN PERUSAHAAN SRI-KEHATI 2021-2023 - Utami, Putri Diar; Supaijo, Supaijo; Zuliansyah, A. Zuliansyah (ITB AAS Indonesia Surakarta, 2025)
The decline in the SRI-Kehati Index quality reflects complex challenges involving market dynamics, global economic conditions, and the industrial sector's response to sustainability and good corporate governance issues. In the implementation of sustainability performance, Green Intellectual Capital emerges as a key determinant of a company's sustainability and financial performance. Organizations that adopt green business concepts such as Green Human Resource Management (GHRM) are likely to achieve greater financial savings and generate profits. Many industries are shifting to adopt a green mindset. Increasingly, companies are considering Green Innovation as a critical approach to reduce negative impacts on the environment. Based on these factors, the objective of this research is to examine the influence of green intellectual capital, green human resource management, and green innovation on the sustainability performance of SRI-Kehati companies from 2021 to 2023. This study employs a quantitative approach and utilizes secondary data from sustainability performance reports of companies, which is then analyzed using multiple regression analysis. The results indicate a significant influence of green intellectual capital, green human resource management, and green innovation on the sustainability performance of SRI-KehatiÂ companies.